Matéria Elétrica e Forma Magnética: Experimentos e concepções de William Gilbert no De Magnete - Magalhães, Antônio de Pádua (2007)
William Gilbert of Colchester (1544-1603), one of the many personal physicians of Queen Elizabeth the First, was a prominent figure regarding the studies of electric and magnetic phenomena between the end of the XVI century and the beginning of the XVII century. In his attempt to reformulate the approach given to knowledge about the nature of these phenomena in his days, as well as the appropriate way to elaborate such process, William Gilbert would then develop various original and influent works, which would be published in the year of 1600 in his book De Magnete. His declared purpose would be to establish a new philosophy based on arguments and true observations, demonstrated by experiments and experiences. Consequently, he would then create new concepts and conceptions about the nature of electric and magnetic matter. The present work aims to go further in the analysis of this specific book, undertaking initially some aspects of its structure, editions and repercussions, as well as the rare biographical data on the author. Next, we investigate the relationship between De Magnete and some of the sources suggested by the author. Particularly those concerning the experiments regarding the magnetic phenomenon, specially the Epistola attributed to the medieval thinker Petrus Peregrinus, The New attractive (1581), written by the navigation craftsman Robert Norman. We also take into consideration, William Gilbert s criticism of book VII of Magia Naturalis (1558) written by the renaissance magician, Giambattista della Porta. We finally deal with the conceptions of electric matter and magnetic form proposed by William Gilbert. The study of the attractions would force him to separate electric bodies, imperfect for acting through matter, from magnetic bodies, perfect for acting through form. Therefore, form should present similarity with a superior soul and a resemblance with the skies